2021
DOI: 10.1016/j.jtumed.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms and excessive daytime sleepiness in a cohort of Saudi doctors under training: A cross sectional study

Abstract: Objectives Recent studies have highlighted an increasing prevalence of depression and sleep problems among physicians during their residency training in the medical field. The study aims to explore the prevalence of depressive symptoms and sleepiness among the residents of different medical specialties in the two regions of KSA and describe the factors that potentially cause depression and sleepiness. Methods A survey was distributed to the residents of King Abdulaziz M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…According to Hameed, et al [3] study that indicated that depressive symptoms were more likely seen in the residents of King Abdulaziz Medical City in Riyadh and King Fahad Specialist Hospital along with maternity and children's hospital Buraidah with a prevalence rate of about 95%, which is contradicting with our results that revealed low prevalence of depression among the study population. It should be noted that Hameed et al study was conducted on two hospital settings, i.e., in Riyadh and Qassim, and on different surgical and medical specialties' residents.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…According to Hameed, et al [3] study that indicated that depressive symptoms were more likely seen in the residents of King Abdulaziz Medical City in Riyadh and King Fahad Specialist Hospital along with maternity and children's hospital Buraidah with a prevalence rate of about 95%, which is contradicting with our results that revealed low prevalence of depression among the study population. It should be noted that Hameed et al study was conducted on two hospital settings, i.e., in Riyadh and Qassim, and on different surgical and medical specialties' residents.…”
Section: Discussioncontrasting
confidence: 99%
“…Among 181 residents in King Abdulaziz Medical City in Riyadh, 93% of them had depressive symptoms. In comparison to 146 residents from King Fahad Specialist Hospital and Maternity and Children's Hospital in Qassim, 94.5%, and 84.4% respectively had symptoms of depression [3]. Another study done on resident physicians in 2020 at King Fahad Medi-cal City (KFMC), Riyadh, showed the prevalence of depression among family medicine doctors was 18.5% [4].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 However, not all hospitals and healthcare organizations abide by these working hours and, as a result, physicians end up working much longer beyond them. 17 The advised working hours in many developed countries vary between 35 to 40 hours a week. 9 The European Commission has suggested that the duration should not exceed 48 hours per week, including overtime.…”
Section: Introductionmentioning
confidence: 99%
“…16 Unfortunately, physicians in Saudi Arabia, like in other countries, work much more than these upper limits. 17,21 The mental health of an individual can become severely compromised as a result of constant work pressures and related stressors. 22 Working long hours is one of the main work stressors that negatively impact mental health, particularly concerning anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%